Critical Evaluation Psychology on Vagrancy Intervention Programs: The Case in Malaysia - Zulayti, Zakaria; Kean Hua, Ang; Mohamad Pirdaus, Yusoh; Junaidah, Yusof; Norena, Abdul Karim Zamri; Mohd Fadzil Ali, Ahmad (Auricle Global Society of Education and Research, 2023)
Purpose: This paper seeks to address that the studies on vagrancy in Malaysia should be undertaken by community-based clinical approach, replacing the current unworkable and costly failure of economic approach. The failure to recognise and address this fact has caused the problems of vagrancy in this country left almost untreated. Design/Methodology/Approach: This study is based on the data collected from the fields works in the capital city of Malaysia, Kuala Lumpur. The data are collected by ‘intuitive interface experience and observation,’ a method of collecting the data from what being observed, heard and experienced from our own acquaintance by living with the vagrants. The data then being analysis through community-based clinical approach, an approach that gives attention to the complex interplay of psychic of the individuals and sociocultural condition. Findings: The findings of this study opposesthe conventional advocacies which applauded that vagrancy in Malaysia is caused by economic factors such as high rental for dwelling places (both for house and room), lack of employment opportunities, high cost of living, low wages. Instead, the data collected from this study reveal that it has been the psychotic disorders that have created all those economic problems. Research Practical and Social Implications: This paper concludes that the most immediate and critical measures that urgently need to be done by the government agencies is to increase the number of specialized practitioners and workers in psychotic disorders and mental illness, namely, the psychiatrists, psychologists as well as nurses and medical attendants.Originality/Value: This researchis the first study to be conducted in Malaysia, specifically focusing at Kuala Lumpur Metropolitan City area. At the same time, this study examines the status of vagrance cases in Malaysia as an important to the academic knowledge development.